Pelatihan Manajemen Komunikasi pada Badan Permusyawaratan Desa (BPD) dalam Meningkatkan Pemberdayaan Masyarakat - Ari Sulistyanto; Aan Widodo; Saeful Mujab; Dwinarko Dwinarko (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: The ability in planning communication, organizing messages, implementing and supervising members of the Village Community Empowerment Agency (BPD) is needed so that they are able to build synergies with the community and village heads for village development in Subang Regency. Method: To improve this ability, communication management training activities were carried out. The method was carried out through lectures and discussions. Results: The results obtained were an increase in positive understanding related to communication management carried out in community empowerment and the satisfaction with the material presented. This is indicated by 92.3%, that the material presented provides benefits and new understanding in community empowerment. Conclusions: Through this training activity, members of the Village Community Empowerment Agency (BPD) are able to improve their abilities in planning communication and organizing messages in carrying out their duties as BPD members in the implementation and supervision of village development.